High density of ice krill (Euphausia crystallorophias) in the Amundsen sea coastal polynya, Antarctica. (January 2015) - La, Hyoung Sul; Lee, Hyungbeen; Fielding, Sophie; Kang, Donhyug; Ha, Ho Kyung; Atkinson, Angus; Park, Jisoo; Siegel, Volker; Lee, SangHoon; Shin, Hyoung Chul
Abstract: High densities of ice krill Euphausia crystallorophias were observed along six acoustic transects within the Amundsen Sea Coastal Polynya, Antarctica. Two-frequency acoustic backscatter data was examined in the austral summers of January 2011 and February 2012. A dB identification window ( S v120−38 ) identified ice krill dominating the acoustic backscatter. The density of ice krill, calculated with the stochastic distorted-wave born approximation model, ranged between 4.5 and 30 g wet mass m −2 for each transect (a mean of 16 g wet mass m −2 for all transects), these high values are an order of magnitude higher than recorded previously in the Ross Sea Polynya. High densities were detected along the ice shelf and near the boundary between pack ice and coastal polynya, and we postulate that these could be important habitats for ice krill. The high densities observed along the transects make ice krill a potentially important, but poorly known contributor to these high-latitude shelf food webs. Highlights: Acoustic surveys were conducted to observe the density variation of ice krill in the Amundsen Sea Coastal Polynya, which is the most productive polynya in the Southern Ocean. Ice krill dominated the Polynya, which we could verify by net samples, and a dB difference identification and threshold technique was used to separate ice krill and Antarctic krill in the acoustic data. The ice krill density in the Amundsen Sea Coastal Polynya was an order of magnitude higher than that in other coastal polynyas.